An AI-driven, de novo designed all-in-one nanoplatform for cold tumor therapy - Tian Lu; Ruining Jia; Yufei Wu; Yumeng Wang; Jiyi Zhang; Qiyu Chen; Ruonan Li; Yaonan Wang; Yuji Wang (Chemical Engineering Journal, 2026)

Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

On-site and embodied water demand of urban residential buildings in China under the Shared Socioeconomic Pathways - Hui Li; Ruining Zhang; Xueting Peng; Yangyang Guo (Environmental Impact Assessment Review, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Excavation-induced principal stress rotation and deformation responses in shallow-buried tunnels - Hongguang Jiang; Siwei Ruan; Ruining Liu; Xizhen Song; Yixin Li; Shun Liu; Xinyu Wang; Chenglu Gao; Zhanyong Yao; Chuanyi Ma (Transportation Geotechnics, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

An experimental and kinetic modeling study of the autoignition delay times of triethyl phosphite - Frederick Nii Ofei Bruce; Yuke Gao; Ruining He; Zhihan Zhu; Xin Wang; Yilin Zhao; Mengmeng Jia; Jiaxin Xie; Xin Bai; Yun Hin Taufiq-Yap; Chong-wen Zhou; Henry Curran; et al. (Fuel, 2026)

An exploration into the transplacental transfer of microplastics through placental transporters - Binbin Guo; Yawei Wang; Weilin Wang; Ruining Guan; Dongquan Li; Qiyue Wang; Chunyan Zhao (Journal of Environmental Sciences, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

An experimental and kinetic modeling study of the autoignition delay times of trimethyl phosphite - Frederick Nii Ofei Bruce; Zhihan Zhu; Ruining He; Xin Wang; Yuke Gao; Chong-Wen Zhou; Yun Hin Taufiq-Yap; Henry Curran; Yang Li (Fuel, 2026)

Integrated analysis of laboratory and field experiments to screen rice germplasm for submergence tolerance across various growth stages - Shengqin Liu; Hao Ai; Sumei Duan; Ruining Li; Edwin Afriyie Owusu; Liangliang Lv; Zhanglun Sun; Dachao Xu; Mengzhu Zhang; Aifeng Zhou; Wei Wang; Tingting Feng; et al. (Field Crops Research, 2026)

Bifunctional modulation of MrBBX19 on repressor MrNAC47 and activator MrMYB12 for UV-B-mediated quercetin enhancement in Chinese bayberry (Morella rubra) - Ruining Zhang; Qianyu Wang; Jiajia Li; Jiafei Qian; Xiangrui Cui; Yunlin Cao; Yilong Liu; Xiaoyong Zhao; Di Wu; Changjie Xu; Kunsong Chen; Xian Li (Food Chemistry, 2026)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

Effects of high hydrostatic pressure on starch: multi-scale structures, interactions and applications - Yuqian Zheng; Xiaoyan Qin; Wenyan Wang; Zhilong Chen; Wenlong Xie; Jun Zhao; Ruining Zhang; Sheng Li (Food Chemistry, 2025)

Exploring the toxicological network of bleomycin-induced pulmonary fibrosis: The role of long non-coding RNAs - Bingxin Li; Hongbin Shi; Yun Ma; Ruining Zhao; Haijun Zhang (Food and Chemical Toxicology, 2025)

Soybean insoluble Fiber-EGCG binary compounds: Enhanced stability and synergistic antioxidant activity - Yi Wang; Ruining Zhang; Shidi Men; Mingzhe Li; Guannan Liu; Xiangbo Zeng; Bo Lyu; Sainan Wang; Hansong Yu (Food Chemistry, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

SAR ship detection across different spaceborne platforms with confusion-corrected self-training and region-aware alignment framework - Shuang Liu; Dong Li; Haibo Song; Caizhi Fan; Ke Li; Jun Wan; Ruining Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

MbWRKY50 confers cold and drought tolerance through upregulating antioxidant capacity associated with ROS scavenging - Xinhui Wang; Yingnan Li; Zhuo Chen; Longfeng Li; Qiqi Li; Zihan Geng; Wanda Liu; Ruining Hou; Lihua Zhang; Deguo Han (Journal of Plant Physiology, 2025)

Polystyrene and polyethylene perturb the structure of membrane: An experimental and computational study - Ruining Guan; Qiyue Wang; Dongquan Li; Binbin Guo; Weilin Wang; Ningqi Li; Jinlong Zhang; Ruitong Cai; Zeyang Cui; Haixia Zhang; Chunyan Zhao (Environmental Pollution, 2025)

Phytochemical investigation of Jie-Geng-Tang and regulatory role in the TNF-α pathway in mitigating pulmonary fibrosis using UPLC-Q-TOF/MS - Bingxin Li; Ruining Zhao; Xiaojie Jiang; Chang Liu; Yun Ma; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Long-term soy dietary fiber diet modifies the intestinal internal environment: Focus on chronic ulcerative colitis - Yi Wang; Ruining Zhang; Mingzhe Li; Jiaxin Li; Guannan Liu; Sainan Wang; Bo Lyu; Hansong Yu (Food Research International, 2025)

Augmentation of antiviral immune response induced by perturbation of CD82 under microgravity condition - Yuzhi Zhang; Sijie Wang; Jiawei Chen; Yidan Zhou; Xiaoyu Yu; Ruining Peng; Longfeng Lu; Shun Li; Zhenhao Tian; Nu Zhang; Hui Yang (Fish & Shellfish Immunology, 2025)

A Large-Scale Focused Fluid Flow Zone Between Atolls in the Xisha Islands (South China Sea): Types, Characteristics, and Evolution - Jixiang Zhao; Benjun Ma; Zhiliang Qin; Wenjian Lan; Benyu Zhu; Shuyi Pang; Mingzhe Li; Ruining Wang (Journal of Marine Science and Engineering, 2025)
A large number of seabed depressions, covering an area of 2500 km2 in the Xisha Massif of the South China Sea, are investigated using newly collected high-resolution acoustic data. By analyzing the morphological features and seismic attributes of the focused fluid flow system, five geological structures are recognized and described in detail, including pockmarks, volcanic mounds, pipes, faults, and forced folds. Pockmarks and volcanic mounds occur as clustered groups and their distributions are related to two large-scale volcanic zones with chaotic seismic reflections. Pipes, characterized by disordered seismic reflections, mainly occur within the focused fluid flow zone (FFFZ) and directly link with the large-scale deep volcano and its surrounding areas. Faults and fractures mainly occur along pipes and extend to the seafloor, commonly presenting lateral walls of mega-pockmarks. Forced folds are primarily clustered above volcanic zones and commonly restricted between faults or pipes, characterized by sediment deformations as indicated in seismic profiles. By comprehensive analysis of the above observations and a simplified simulation model, the volcanism-induced hydrothermal fluid activities are argued herein to contribute to these focused fluid flow structures. In addition, traces of suspected submarine instability disasters such as landslides have been found in this sea area, and more observational data will be needed to determine whether seafloor fluid flow zones can be used as a predictor of seafloor instability in the future.

Toxicity assessment and i-QSTTR analysis of ionic liquids on D. magna, D. rerio, and R. subcapitata - Ruining Guan; Ningqi Li; Ruitong Cai; Binbin Guo; Qiyue Wang; Dongquan Li; Chunyan Zhao (Science of The Total Environment, 2025)

Exploring the preventive effects of Jie Geng Tang on pulmonary fibrosis induced in vitro and in vivo: a network pharmacology approach - Bingxin Li; Xiaojie Jiang; Chang Liu; Yun Ma; Ruining Zhao; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A comprehensive experimental and theoretical study of thermal response mechanisms of TKX-50 and HMX - Xuan Ren; Ruining He; Xinhui Wang; Fang Wang; Xinpeng Zhang; Dingcheng Wang; Shuyuan Liu; Henry J. Curran; Jinhu Liang; Yang Li (Fuel, 2024)

Phage LysSA163-CBD mediated specific recognition coupled with ATP bioluminescence for the sensitive detection of viable Staphylococcus aureus in food matrices - Peng Guan; Ruining Li; Yifeng Ding; Chenxi Huang; Jia Wang; Hui Pan; Yanchun Shao; Xiaohong Wang (Analytica Chimica Acta, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

Intertwined role of mechanism identification by DFT-XAFS and engineering considerations in the evolution of P adsorbents - Ruining Zhao; Benhang Li; Siyuan Chen; Boxuan Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Science of The Total Environment, 2024)

Physiological and biochemical responses of arbuscular mycorrhizal fungi in symbiosis with Juglans nigra L. seedlings to alleviate salt stress - Ao Li; Chengxu Wu; Xu Zheng; Ruining Nie; Jiali Tang; Xinying Ji; Junpei Zhang (Rhizosphere, 2024)

Natural mineral and industrial solid waste-based adsorbent for perfluorooctanoic acid and perfluorooctane sulfonate removal from surface water: Advances and prospects - Siyuan Chen; Benhang Li; Ruining Zhao; Boxuan Zhang; Yuqing Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Chemosphere, 2024)

Global assessment of radiative cooling and low-emissivity coatings for energy efficiency in buildings across all climate zones - Jiashuo Wang; Zekai Li; Tongyu Zhou; Wu Deng; Runqi Liang; Isaac Yu-Fat Lun; Yilin Li; Ruining Bao (Energy and Buildings, 2024)

Cleaner reactive dyeing with the recycled dyeing wastewater - Dawu Shu; Wanxin Li; Bo Han; Fangfang An; Yan Zhang; Shaolei Cao; Ruining Liu (Journal of Environmental Chemical Engineering, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Performance and mechanisms of zero valent iron enhancing short-chain fatty acids production during thermophilic anaerobic fermentation of waste activated sludge - Wanqing Ding; Xiumin Fan; Xu Zhou; Ruining Liu; Chuan Chen; Wenbiao Jin; Jing Sun; Xuan Li; Guangming Jiang; Huan Liu (Science of The Total Environment, 2024)

Efficient low-concentration phosphate removal from sub-healthy surface water by adsorbent prepared based on functional complementary strategy - Benhang Li; Yanhao Chen; Gengbo Ren; Ruining Zhao; Zhineng Wu; Fujie Zhu; Xiaodong Ma (Science of The Total Environment, 2023)

Probing the combustion kinetics of dimethylformamide: A theoretical study of H-atom abstraction reactions - Xin Bai; Yang Li; Shuyuan Liu; Ruining He; Jinhu Liang; Geyuan Yin; Shijie Zheng; Yan Qian; Xuebin Wang (Fuel, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Non-steady state fluctuations in water levels exacerbate long-term and seasonal degradation of water quality in river-connected lakes - Yingze Yin; Rui Xia; Yan Chen; Ruining Jia; Nixi Zhong; Chao Yan; Qiang Hu; Xiang Li; Hui Zhang (Water Research, 2023)

How to design subsidy policies for clean energy projects? A study on “coal-to-gas” project in China - Ruining Zhang; Xianneng Ai; Hui Li (Resources Policy, 2023)

Depositional conditions of siliceous microfossil-rich shale during the Ordovician–Silurian transition of south China: Implication for organic matter enrichment - Ruining Hu; Jingqiang Tan; Jeffrey Dick; Yong Wang; Guolai Li; Chiyang Liu (Marine and Petroleum Geology, 2023)

Norfloxacin degradation in synthetic human urine using nickel converter slag-laterite heterogeneous Electro-Fenton process - Lingke Miao; Junfeng Li; Chengxiao Ma; Wenying Qu; Wenhuai Wang; Jiankang Wang; Ruining He (Journal of Water Process Engineering, 2023)

Parasitoid ecology along geographic gradients: lessons for climate change studies - Lena Jego; Ruining Li; Sacha Roudine; Chun-Sen Ma; Cécile Le Lann; Gang Ma; Joan van Baaren (Current Opinion in Insect Science, 2023)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Magnetic biochar-based manganese oxide composite for enhanced fluoroquinolone antibiotic removal from water - Ruining Li; Zhaowei Wang; Xiating Zhao; Xi Li; Xiaoyun Xie (Environmental Science and Pollution Research, 2018)

Molecular Cloning and Identification of the 2′–5′ Oligoadenylate Synthetase 2 Gene in Chinese Domestic Pigs Through Bioinformatics Analysis, and Determination of Its Antiviral Activity Against Porcine Reproductive and Respiratory Syndrome Virus Infection - Ruining Wang; Hongfang Ma; Yinfeng Kang; Cunfa Li; Huawei Li; Erqin Zhang; Pengchao Ji; Jian He; Mengmeng Zhao (Indian Journal of Microbiology, 2018)

Influence of Rainfall, Model Parameters and Routing Methods on Stormwater Modelling - Yongwei Gong; Xiaoning Li; Dandan Zhai; Dingkun Yin; Ruining Song; Junqi Li; Xing Fang; Donghai Yuan (Water Resources Management, 2018)